Serous Retinal Detachment in Pre-eclampsia: Case Report and Literature Review - Raposo, Joana Teresa Botelho Vasconcelos; Melo, Bruna Carina Da Silva; Maciel, Nuno Filipe Bernardo Belo; Leite, Sara Dias; Rebelo, Óscar Renato Coutinho; Lima, Ana Maria Furtado (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Pre-eclampsia (PE) is an obstetric disease with a multifactorial cause that affects ∼ 5% of pregnant women. Vision can be affected with varying severity, and retinal detachment is a very rare complication. It tends to be bilateral, diagnosed postpartum, and more prevalent in women who are primiparous and/or undergo caesarean delivery. The condition typically resolves completely and rarely causes total visual loss in the affected women. Fluorescence angiographic findings support the hypothesis that retinal detachment in PE is secondary to choroidal ischemia from intense arteriolar vasospasm. The present article is related to a case of a 37-year-old pregnant woman who had PE associated with a progressive blurred vision, diagnosed by ophthalmology as serous macular detachment of the retina.
Keywords: pre-eclampsia; retinal detachment; pregnancy complications; decreased visual acuity